Prática de atividade física e função física em grupo de idosos praticantes de atividade física durante a pandemia por COVID19 no interior do Amazonas - Silva, Tatiana Araújo da (Brasil, 2022)
Objective: To describe the presence of physical activity and physical function in a group of elderly practitioners of physical activity during the covid19 pandemic in the interior of Amazonas. Method: This is a cross-sectional study carried out with active elderly people who performed physical activity at least 3 times a week for 50 minutes in the interior of Amazonas. The practice of physical activity was evaluated before and during the pandemic and with 2 questions regarding Covid-19. To assess the functional and physical capacity, the Short Physical Performance and Battery (SPPB) was applied. Results: The sample consisted of 63 elderly people who practice physical activities. Of these, 31.8% (21) of the elderly are illiterate, 74.2% (49) are retired and 75.8% (50) have low income. In the SPPB, 27.3% (18) had a total of 10 points, thus presenting good muscle performance of the lower limb and 14.29% (9) of the elderly perform physical activities above the minutes recommended by the World Health Organization (WHO). ). Conclusion: In this study, no factor during the pandemic interfered with the practice of physical activities or the functional capacity of these elderly people living in the interior of Amazonas.